Monitoring, modelling and prediction of segmental lining deformation and ground settlement of an EPB tunnel in different soils. (July 2021) - Mu, Baogang; Xie, Xiaokun; Li, Xing; Li, Jianchun; Shao, Chengmeng; Zhao, Jian
Highlights: The deformation characteristics of lining structure of EPB tunnel are analyzed. The optimal model of deformation and settlement of lining is established. The numerical model is used to study the influence of different factors on lining. Abstract: In this paper, the deformation characteristics of tunnel lining structures in different soils are studied by theoretical analysis, numerical modelling and field monitoring. The deformation of segmental lining was monitored by distributed optical fiber sensors in the tunnels of Foshan Metro Line 2 during EPB shield tunnelling. The structural deformation characteristics, including the longitudinal strain and curvature, the circumferential and longitudinal joint deformation, the longitudinal settlement, and the circumferential convergence of the tunnel under different ground conditions and at different depths are analysed based on the monitoring data. The optimized conjugate beam method is developed to analyse the lining deformation and the ground settlement. The PLAXIS 3D finite element model is utilized to study the effects of soil properties (cohesion and friction angle), tunnel depth and soil reinforcement on the tunnel lining deformation and ground settlement. Numerical modelling is further applied to simulate and predict the lining deformation of Foshan Metro Line 2 tunnels, which are compared with the monitoring data. The prediction results can effectively help to reduce the risks of large deformation and settlement in weak and soft grounds.